2022
DOI: 10.1002/14651858.cd015243
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding in infants diagnosed with phenylketonuria

Abstract: To assess the e ects of breastfeeding (exclusive or partial) compared to low-Phe formula feeding in the first six months a er birth in infants diagnosed with PKU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…We performed this scoping review with a similar protocol as our review protocol for a systematic review 4 for the same research question, except in the plan to include all study types and not restrict the review to RCTs as was previously done. We included all studies where the participants were infants diagnosed with PKU (via newborn screening programme or later) in the first 6 months after birth and their mothers.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We performed this scoping review with a similar protocol as our review protocol for a systematic review 4 for the same research question, except in the plan to include all study types and not restrict the review to RCTs as was previously done. We included all studies where the participants were infants diagnosed with PKU (via newborn screening programme or later) in the first 6 months after birth and their mothers.…”
Section: Methodsmentioning
confidence: 99%
“…We followed a similar search strategy as performed for our systematic review with the Cochrane Collaboration. 4 We searched the following databases and trial registries: MEDLINE Ovid (1946 to present); Embase Ovid (1974 to present); US National Institutes of Health Ongoing Trials Register ClinicalTrials.gov ( www.clinicaltrials.gov ); WHO International Clinical Trials Registry Platform ( trialsearch.who.int/ ). We checked the bibliographies of included studies and any relevant systematic reviews identified for further references to relevant trials.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies on the subject have shown that medical foods with a low phenylalanine formula can improve the health status of children with PKU (Chen et al 2015;MacDonald et al 2020;Mtewa et al 2020). Specified medical food formulas that do not contain disease-causing protein derivatives should be used in other amino acid metabolism disorders such as non-ketonic hyperglycinemia, tyrosinemia, and maple syrup urine disease (McCandless et al 2021;Chong et al 2022).…”
Section: Medical Foods For Congenital Metabolic Disordersmentioning
confidence: 99%